Implementation of Pancasila in the Development of Science and Technology - Yuriska Septiana Wulan Dari; Novinda Triyan Rachmadani (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract – Entering an increasingly modern era, life now refers to the digital world, as well as science and technology (IPTEK). The development of science & technology has made big changes to the lives of everyone in the world, including the people of Indonesia, every individual strives to continue to develop technological literacy abilities. The development of science and technology that exists today, apart from being able to have a positive impact and various conveniences for human life, we cannot deny that the development of science & technology can also bring about various negative things. Therefore, science & technology needs to adjust and consider the ideological values ​​of the nation in its development, both from the aspect of religious and cultural values, all must be relevant and always refer to the noble values ​​of the nation so as not to harm humans and damage the joints of the nation's life. Pancasila, which is the basis of the state and the nation's view of life, contains noble values ​​that are believed to be the nation's protective shield, of course, must also play a role in facing technological progress. This article aims to explain that Pancasila plays an important role in technological progress and towards a more modern Indonesian human.Although the younger generations are technologically literate, if they do not have the character of Pancasila and the spirit of nationalism, then everything will be in vain. So that the implementation of Pancasila as a whole is really needed to continue to direct the nation's young generation to stick to the Pancasila path with character. Keywords: Pancasila values, Technology, The times